2018
DOI: 10.1088/1361-6560/aad1be
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic 18F-FLT PET imaging of spatiotemporal changes in tumor cell proliferation and vasculature reveals the mechanistic actions of anti-angiogenic therapy

Abstract: Anti-angiogenic therapies target tumor vasculature and tumor cells, thus a concurrent assessment of these targets would lead to a greater understanding of therapeutic resistance and facilitate development of improved therapeutic strategies. We utilize dynamic 3'-deoxy-3'-F-fluorothymidine positron emission tomography (F-FLT PET) scanning to concurrently assess changes in tumor cell proliferation and vasculature during anti-angiogenic therapy, providing insight into how these therapies may be used effectively w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The design and preparation of custom OP PET tracers was undertaken with the goal of examining: a) PK distributions, b) PD fates including the in vivo inactivation and labeling of AChE rich tissues, c) spatio-temporal imaging (Clarkson and Kupinski, 2009; Scarpelli et al, 2018) ( e.g ., Fig. 4) and, d) conducting challenge studies in which displacement or blocking of the OP tracer from AChE-rich regions could be observed and quantified.…”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…The design and preparation of custom OP PET tracers was undertaken with the goal of examining: a) PK distributions, b) PD fates including the in vivo inactivation and labeling of AChE rich tissues, c) spatio-temporal imaging (Clarkson and Kupinski, 2009; Scarpelli et al, 2018) ( e.g ., Fig. 4) and, d) conducting challenge studies in which displacement or blocking of the OP tracer from AChE-rich regions could be observed and quantified.…”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…The assessment of pharmacodynamic endpoints is another extremely important function for [ 18 F]FLT. Scarpelli et al [38,39] demonstrated that the increase of [ 18 F] FLT uptake is apparently caused by the washout period during treatment. This type of study, which evaluates the pharmacodynamic endpoints, is of great importance to develop better understanding of drug resistance mechanisms, as it helps clinicians to tailor more effective treatments and to minimise systematic toxicity caused by ineffective drugs [38].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have found high potential of [ 18 F]FLT to predict LC response to targeted therapy. Yang et al analysed the prediction of response to anti-angiogenic [38,39]. In the static PET study, SUVmax was decreased −11% in cycle 1 treatment with the anti-angiogenic x-82.…”
Section: Targeted Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In line with our hypothesis, we report a significant reduction in K 1 following TACE, illustrating abrupt reduction in tissue perfusion. This is in sharp contrast with anti-angiogenic chemotherapy where an increase in the K 1 due to vessel normalization and reduced interstitial pressure can accompany response (27). Dynamic studies using 11C-acetate report a reduced K 1 in HCC lesions supplied by the hepatic artery compared with benign lesions supplied by the portal vein as the radiotracer concentration time-course is initially delayed in the portal vein as passes through the splanchnic circulation(28).…”
Section: Discussionmentioning
confidence: 99%